2021
DOI: 10.3390/foods10112716
|View full text |Cite
|
Sign up to set email alerts
|

Proximate Composition and Nutritional Attributes of Ready-to-Cook Catfish Products

Abstract: To increase the demand for U.S. farm-raised catfish, five healthy, convenient ready-to-cook products were developed to expand consumers’ options beyond basic fresh or frozen fillets. Five new catfish products were produced, consisting of one hundred samples of each, including three size-types of Panko-breaded fish products (strips, center cuts of regular fillets, and center cuts from Delacata fillets) and two marinated products (sriracha and sesame-ginger). The breaded products were to be prepared by baking fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Also, there was a relationship between the protein, fat and moisture content versus the age of fish. The value of protein and fat content increased while the moisture content decreased as supported by Kim et al 56 , who reported that the percentage of fat and protein content increased while the water content reduced as the body weight increased, in addition, protein ash and fat increase when moisture decreases 57,58 . The highest value was obtained in winter while the lowest value gotten in summer.…”
Section: Discussionmentioning
confidence: 78%
“…Also, there was a relationship between the protein, fat and moisture content versus the age of fish. The value of protein and fat content increased while the moisture content decreased as supported by Kim et al 56 , who reported that the percentage of fat and protein content increased while the water content reduced as the body weight increased, in addition, protein ash and fat increase when moisture decreases 57,58 . The highest value was obtained in winter while the lowest value gotten in summer.…”
Section: Discussionmentioning
confidence: 78%
“…Market accessibility and infrastructure play a role in time and labor, for both vendors and consumers of aquatic foods. The degree of processing (e.g., drying, salting, smoking) in the supply chain can reduce time burden in household preparation, which in turn, may increase demand of consumers for convenient fish products (Bland et al, 2021).…”
Section: Conveniencementioning
confidence: 99%
“…The cutting gap between the main blade and the driver roller can be controlled by detecting fish fillet size [ 64 , 65 ]. To get a better quality of the fillets as value-added products, the deep-skinning process can remove the skin with a layer of subcutaneous fat [ 66 , 67 ]. Due to the relatively simple structure, some fish skinning machines are small and can be placed directly on the processing table.…”
Section: Modern Fish Cuttingmentioning
confidence: 99%